China's southwest - Harper, Damian; Ho, Tienlon; Huhti, Thomas; Miller, Korina; Quinn, Eilis ([S.l.] : Lonely Planet, 2007)
Discover China's Southwest Follow your shadow floating over limestone peaks on a Guangxi ballooning voyage. Hike Tiger Leaping Gorge to the snowcapped mountaintops of Haba Shan via the Jinsha River. Savour the Yin and Yang of spicy, sizzling or soaked-in-soy Southwest delicacies. Get caught up in the dancing at the vibrant Miao Lusheng Festival. In This Guide Five intrepid authors, 220 days of in-country research, 157 bus rides and one rotting yak's head. Includes captivating new destinations not covered in any other English-language guidebook. Chapters dedicated to gateway cities (Beijing, Honk Kong and Shanghai), minority cultures and adventure activities.